Keefektifan Model PBL terhadap Kemampuan Literasi Numerasi Peserta Didik Kelas X Materi Trigonometri - Emi Rahmawati; Supandi Supandi; Loesy Poerhandajani; Nizaruddin Nizaruddin (Departement of Mathematics Education, 2024)
Numeracy literacy is important to improve the ability to think critically and make rational decisions. The employment prospects, mental, physical and economic health of individuals and countries are negatively affected by low numeracy skills. Therefore, teachers must focus on increasing students' numeracy literacy with effective strategies and activities. Therefore, the aim of this research is to test the effectiveness of the PBL model on the numeracy literacy abilities of class X students in trigonometry material. This research uses a quantitative approach, quasi-experimental method, with a sampling technique, namely total sampling, as well as a population and sample of class Based on the results of the research that has been carried out, it can be concluded that the Problem Based Learning (PBL) model is effective on the numeracy literacy abilities of class score ≥ 75 (KKM). 2) The average numeracy literacy ability of students in the PBL model is higher than the average numeracy literacy ability of students in the conventional model. 3) The proportion of completeness of students' numeracy literacy test results in the PBL model is more than the proportion of completeness of students' numeracy literacy test results in the conventional model. Keywords: Problem Based Learning, Numeracy Literacy, Effectiveness.